Kajian Pengelolaan Limbah Domestik dan Limbah Bahan Berbahaya dan Beracun (B3) PT X Adisty Regina Tamandita, Rizka Novembrianto - Adisty Tamandita; Rizka Novembrianto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
PT X is a branch of the industry engaged in the field of laying hens which provides livestock products and needs. The production process carried out by PT X results in a product and other production process that can no longer be used or discarded. Waste generated from the production process of PT X is divided into domestic waste and hazardous waste. If this waste is not handled properly and properly, it can have a negative impact on the environment and human health. The purpose of this research is to know and understand the waste management system and to implement the evaluation of the waste operational system. Data collection through observation in the form of a general introduction to the location and field orientation based on company data obtained from PT X. The variables of this study include production, storage, and waste management at PT X and the regulations in force largely comply with this. The results of this study are that PT X has managed Domestic Waste dan B3 Waste based on applicable regulations but there are several points that are not appropriate.